An international perspective on ethics approval in animal behaviour and welfare research - Olsson, I. Anna S.; Nielsen, Birte L.; Camerlink, Irene; Pongrácz, Péter; Golledge, Huw D.R.; Chou, Jen-Yun; Ceballos, Maria Camila; Whittaker, Alexandra L. (Applied animal behaviour science, 2022)
Ethics assessment is essential in studies that involve animals as subjects, which includes research on animal behaviour and welfare. Although ethics review mechanisms within institutions are long established in many regions, processes may be non-uniform across different cultures, institutions, and geographical contexts. Harmonisation need not be the ultimate goal; instead, attention should be directed towards ways of improving ethics assessment with an animal-centred focus. Moreover, applied animal behaviour and welfare research sometimes involves human subjects (e.g., animal owners, farmers, caretakers, and consumers), the ethics of which is scarcely discussed. The International Society for Applied Ethology (ISAE) has developed and revised its ethics guidelines to be applied to research articles submitted to the Society’s journal and conferences, and acknowledges the need to address this increasingly contentious issue from a global perspective. At the 2021 ISAE Annual Congress, a workshop on the ethical challenges in animal behaviour and welfare research was held twice. Participants (N ≈ 70) from several continents were presented with hypothetical research cases outlining different ethics scenarios. These scenarios were discussed in small groups, with each participant contributing experiences from their respective countries. More questions than answers were generated, and the mere action of involving researchers from different scientific cultures in a conversation is an important step towards greater insight and transparency. Significant variability in local ethics review requirements across jurisdictions was revealed. However, by focussing on improving transparency of reporting for both animal and human involvement in studies, particularly in the ethics statement and procedure description, ethics assessment by reviewers and editors can be enhanced. There is a need for continued dialogue on ethics within the animal behaviour and welfare research community. •Summary of ethics workshops held during the ISAE 2021 Annual Congress.•The ethics review process is pivotal in animal behaviour and welfare studies.•Ethics assessment of animal studies varies from region to region•Discussions of ethics should be at international level but consider local contexts.•More transparency and dialogue on this subject are the way forward.